Etiologies and hearing status in bilateral vestibulopathy: a retrospective study of 315 patients - Moyaert, Julie; Dobbels, Bieke; Peetermans, Olivier; Boon, Bram; Lucieer, Florence; Guinand, Nils; Mertens, Griet; Gilles, Annick; van de Heyning, Paul; Fornos, Angelica Pérez; van de Berg, Raymond; Van Rompaey, Vincent (Frontiers in Neurology, 2023)
-Question: What is the underlying etiology and the hearing status of patients with bilateral vestibulopathy (BV)? -Findings: In this three-center cohort-study that included 315 patients, the most frequent non-idiopathic cause of BV is genetic (31%). A proportion as high as 79% of BV patients suffers from uni-or bilateral associated hearing loss.-Meaning: BV is a heterogenous disease. The majority of BV patients have an associated hearing loss. This justifies the development of a combined vestibulocochlear implant. Furthermore, this implicates that the current research investigating if vestibular loss contributes to cognitive decline should correct for the possible associated hearing loss of study subjects.3